Analisa Pengaruh Hambatan Samping Terhadap Kinerja Lalu Lintas pada Ruas Jalan Pertahanan Kabupaten Deli Serdang - Fitri Wulan Dari; Marwan Lubis; Hamidun Batubara (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
The level of congestion and traffic density on the Pertahanan–Tangkahan road section is significantly high due to intensive vehicle activity, particularly from industrial and factory operations along the road. This study aims to analyze the impact of side frictions on traffic performance on this road segment. The methodology follows the Indonesian Road Capacity Guidelines (PKJI 2023), with data collected over five consecutive days. The results show that the highest traffic volume occurred on Monday between 17:00 and 18:00 WIB, reaching 730.5 pcu/hour, while the highest side friction was recorded on Thursday at the same time with 143.8 incidents/hour. The calculated free-flow speed is 40.74 km/hour, road capacity is 2553.04 pcu/hour, and the degree of saturation (DS) is 0.28. This indicates a Level of Service B, meaning traffic flow is nearing capacity, unstable at times, with occasional stops.